Novel formulations ameliorate osteoarthritis in rats by inhibiting inflammation and oxidative stress - Erten, Fusun; Ozdemir, Oguzhan; Tokmak, Muhammed; Durmus, Ali Said; Ozercan, Ibrahim Hanifi; Morde, Abhijeet; Şahin, Kazım (Wiley, 2024)
The study tested new oral plant-based formulations (F) on rats with monosodium iodoacetate (MIA)-induced osteoarthritis, measuring inflammation, antioxidant levels, paw size, stride, and analyzing knee joint images. Fifty-six female Sprague Dawley rats were allocated into 8 groups: (1) Control, (2) MIA (OA induced with MIA), (3) MIA + F1 [curcuminoids+gingerols+acetyl-11-keto-beta boswellic acid (AKBA)], (4) MIA + F2 (curcuminoids+Withania glycosides+AKBA), (5) MIA + F3 (curcuminoids+total withanolides+AKBA), (6) MIA + F4 (curcuminoids, AKBA), (7) MIA + UCII (type II collagen), and (8) MIA + GCHON (Glucosamine Chondroitin). Treatments F1 to F4 reduced right joint diameter and improved stride length and paw area in OA rats. Despite improvements with treatments F1 to F4, there was no significant difference between these groups (p > .05). In OA animals, F1 to F4 treatments decreased MDA levels and increased antioxidant enzymes activities (p < .001). This was done by reducing levels of inflammatory markers and enzymes like IL-1 beta, IL-6, MMP-8, TNF-alpha, CRP, COMP, and LOX-5, while increasing the anti-inflammatory cytokine IL-10. In conclusion, these plant-based treatments significantly reduced osteoarthritis severity, slowed disease progression by reducing inflammation, and protected joints from damage, showing a protective effect in rats with induced osteoarthritis, likely due to their anti-inflammatory and antioxidant properties.
Keywords: anti-inflammatory; inflammation; osteoarthritis; oxidative stress; plant-based formulations